Pengaruh Kondisi Keuangan Wajib Pajak dan Modernisasi Administrasi Pajak Terhadap Kepatuhan Wajib Pajak Hiburan - Rayhan Saddam Arazy; Ivan Yudianto (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The research was carried out in Bandung City using the research facility of the entertainment venue that is located in Bandung. The study aims to analyze the impact of tax obligation financial conditions and tax administration modernization on entertainment tax compliance in Bandung. Looking at the entertainment tax revenue in Bandung over the past five years has been fluctuating and tax revenues in several years have still not reached the target. This research uses a method of causal comparative analysis, which aims to explain the cause-effect relationship between independent and dependent variables by testing the hypothesis. To collect data using the method of disseminating questionnaires to respondents.Based on the chi-square testing of this study, the variable financial conditions of tax obligations have a significant impact on tax compliance and tax administration modernization have a major impact on entertainment tax obligation compliance in Bandung. And based on the coefficient-contingency test, this study showed that the strong enough relationship between the taxable financial condition variable and taxable compliance is 0.274 and the strongest enough relationship among the tax administration modernization variable to entertainment tax compliance in Bandung is 0.496.